GERAKAN KHARISMATIK DAN SUMBANGANNYA BAGI GEREJA KATOLIK ROMA - Silvester Manca (Jurnal Alternatif Wacana Ilmiah Interkultural, 2014)
Charismatic movement in the catholic Church has been known as a legal spiritual organization.The authos is more than convinced that this movement has renewed the Church in certain cardinal points as "option for the poor,devotion to the Holy Spirit, effrt for the healing broken humanity and for restoring peace and justice to human community"Loving God and loving brothers and sister are two sides of the same coin.Communion with God and the wholeness of human community are closely interrelated.Compassion is the heart of charismatic movement, love is creative.it creates humanity.It creates community.The charismatic movement has been more than convinced that we love because we are made to love, to be able to love is a sign of humanity.The depth ofone's capacity to love is a sign of the depth of onés humanity.These arè the strengths of charismatic movement and as such they can not be denied.